Biocomputing 2003 2002
DOI: 10.1142/9789812776303_0023
|View full text |Cite
|
Sign up to set email alerts
|

A PATH PLANNING-BASED STUDY OF PROTEIN FOLDING WITH A CASE STUDY OF HAIRPIN FORMATION IN PROTEIN G AND L

Abstract: We investigate a novel approach for studying protein folding that has evolved from robotics motion planning techniques called probabilistic roadmap methods (prms). Our focus is to study issues related to the folding process, such as the formation of secondary and tertiary structure, assuming we know the native fold. A feature of our prm-based framework is that the large sets of folding pathways in the roadmaps it produces, in a few hours on a desktop PC, provide global information about the protein's energy la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 7 publications
1
44
0
Order By: Relevance
“…previously reported by Song et al [26]. It should also be noted that although we compute other configurations of the sequence that are energetically favorable (faded states), they are not predicted to form because they are unreachable from the unfolded state.…”
Section: Predicting the Folding Pathways Of The B1 Domain Of Protein Gmentioning
confidence: 59%
“…previously reported by Song et al [26]. It should also be noted that although we compute other configurations of the sequence that are energetically favorable (faded states), they are not predicted to form because they are unreachable from the unfolded state.…”
Section: Predicting the Folding Pathways Of The B1 Domain Of Protein Gmentioning
confidence: 59%
“…We obtained promising results for several small proteins (∼60 amino acids) and validated our pathways by comparing the secondary structure formation order with known experimental results [28] using timed contact analysis. We also demonstrated that this technique is sensitive enough to identify the different folding behaviors of structurally similar Proteins G and L [34].…”
Section: Protein Folding Using Prmsmentioning
confidence: 83%
“…For example, if the roadmap maps the potential energy landscape well, then the percentage of pathways in the roadmap that contain a particular formation order should reflect the probability of that order occurring. Table 2 shows secondary structure formation order results for Proteins G and L [34]. Our results were able to identify the different folding behaviors of the two structurally similar proteins.…”
Section: Protein Folding Using Prmsmentioning
confidence: 91%
See 2 more Smart Citations